Penerapan Konsep Gamifikasi Pada Pembelajaran Merangkai Kata dan Kalimat Aksara Kaganga Rejang Berbasis Android (Studi Kasus: SDN 17 Rejang Lebong) - Andreswari, Desi; Coastera, Funny Farady; Juwita, Fatma (Universitas Bengkulu, 2023)
Abstract: The Ulu script (Kaganga) is one of the heritage scripts in the Southern (coastal) Sumatra region. There are several types of this script, namely Kaganga Rejang, Kaganga Lampung, Kaganga Serawai, Kaganga Pasemah and Kaganga Palembang. In Rejang Lebong, efforts are made to preserve and study Kaganga Rejang in schools as a Local Content subject. However, the lack of interest and low motivation to learn is a factor in hindering the learning process in students. Gamification is the application of concepts by incorporating game elements into non-game problems that have been proven to increase user motivation and retention. Therefore, there is a need for an application for learning the Kaganga Rejang script with a gamification concept that can help students in the learning process. The test results using the SUS (System Usability Scale) method are grade scale